Dehesa ecosystem: Production and preservation - Olea, L; Figuera, F (Options Méditerranéennes, 1999)
The Dehesa is an ecosystem in which species of herbs, bushes and trees coexist in a semi-desert regime, contributingto the feeding of domestic and wild animals. The improvement and exploitation of these agrosylvopastoral systems must be founded on the principles of preseofr vthaetio ne nvironment and the idea of creating systems that can be maintained with a correct usage of natural resources. Fertilization of the natural pastures, the introduction of new pasture species and varieties, the favouring of the species of bush that have a forage value and the preservationo f the arboreous stratum are methods which will alluosw t o preserve this ecosystem
Keywords: Dehesa; forages; iberian peninsula; pastures

Analisis de los recursos de pastoreo aportados por el medio en dos Dehesas caracteristicas del sur de la provincia de Badajoz (España) - Sánchez, M Escribano; García, F Pulido (Archivos de zootecnia, 1994)
En este trabajo se analizan los recursos de pastoreo en dos explotaciones características de dehesa de Extremadura en el año 1992, Desde el punto de vista de la evaluación técnica, se observa que el sistema cubre, con recursos propios, entre el 54 y el 56 p.100 de las necesidades de la ganadería doméstica en el año de estudio, que se caracterizó por una climatología adversa, Por otro lado, los recursos de pastoreo suponen una de las principales utilidades económicas del sistema dehesa, cuya efectividad económica dependerá de la posibilidad de sustitución y del precio de mercado de las materias primas energéticas comerciales.
Keywords: agroforestry systems; Economic analysis; Extensive systems; natural resources; pastures